ANALISIS PENGARUH TIPE BOULDER TERHADAP RECOVERY SCREENING STATION PRODUCT PT. VALE INDONESIA TBK SOROAK - Sabang, St. Hastuti; Maulana, Adi; Irvan, Ulva Ria (Jurnal Penelitian Geosains, 2015)
Rock size distribution is plays an important role in mining unserpentinized peridotite of Sorowako laterite nickel deposite. The increasing of Rock size will reduce mine recovery and make mining operation become more expensive. To outlining the Rock size distribution, a model generated from RQD have been used to classified rock size distribution into 4 unit is WT 1, WT 2, WT 3, and Infracture. The purpose of this study is provide an integrated and detailed information about the actual size of boulder in West Block and distribution of rock boulder. Research areas are in the concession area of West Block of PT. Vale is Hill X, Hill Y, and Hill Z. The research methods used by based on the method of RQD and data processing base on the drill point. Megascopic observations of rock types in the study area is igneus rock peridotite with composition of mineral dominantly by piroksin, olivine, serpentin and opaq. From the results of the data analysis and identifier of each element laterite zona through surface geological mapping Laterite zone of research area can be divided top soil, limonite zone, saprolite zone and bedrock.Keywords: West block of PT. Vale, Laterite nickel, Unserpentinized peridotite, Rock type.